The Malaysian Political Economy: Economic Transformation & the Expansion of Islamic Economics - Abdalrahman Mohamed Migdad; Harun Adams Babngida (Islamic Economics Journal, 2022)
This paper aims to shed light on Malaysian economic development briefly in light of demographics and politics while focusing on economic legislation that had the largest effect on the outlook of the nation known to the world today. Later on, Islamic economics was introduced to the scene and developed wider and faster than most Islamic economies in the world. This paper also explains this rapid development in the context of the nation’s political-economic development.The paper is qualitative and analytical; it addresses developments up to 2017. Although few discussions extend beyond the focused period, they were not significant enough to change the entire perspective. The paper incorporates fieldwork, observations, and interviews that took place in 2017. The paper concludes that certain socio-economic policies need to be updated to suit today's generations and allow for the continuation of development at high rates. Furthermore, the expansion of Islamic economics is beneficial; however, the industry demands detail and procession more than ever, especially in sharia compliance for it to continue developing steadily.